Contactless Series Resistance Imaging of Perovskite Solar Cells via Inhomogeneous Illumination. Issue 12 (27th October 2021) - Mahboubi Soufiani, Arman; Zhu, Yan; Mussakhanuly, Nursultan; Yun, Jae Sung; Trupke, Thorsten; Hameiri, Ziv
Abstract : A contactless effective series resistance imaging method for large‐area perovskite solar cells that is based on photoluminescence imaging with nonuniform illumination is introduced and demonstrated experimentally. The proposed technique is applicable to partially and fully processed perovskite solar cells if laterally conductive layers are present. The capability of the proposed contactless method to detect features with high effective series resistance is validated by comparison with various contacted mode luminescence imaging techniques. The method can reliably provide information regarding the severeness of the detected series resistance through photoexcitation pattern manipulation. Application of the method to subcells in monolithic tandem devices, without the need for electrical contacting the terminals, appears feasible. Abstract : Application of photoluminescence‐based contactless series resistance imaging using nonuniform illumination is demonstrated on perovskite solar cells. The operating point of particular regions is controlled spatially via photoexcitation pattern manipulation across the device. The capability of this proposed contactless method to identify features with high and low absolute effective series resistance is validated qualitatively by comparison with other luminescence‐based imaging techniques.